Perceptions of Workplace, Principal, and Productive Teachers on Students’ Work Readiness in SMK Negeri 5 Surabaya Indonesia - Subijanto Subijanto (Jurnal Pendidikan Teknologi Kejuruan, 2019)
Work readiness of Vocational School (SMK) students will not be formed by itself, but through learning outcomes obtained inside and outside the school in the form of industrial work practices. This is necessary as the practical facilities in Vocational High Schools are inadequate and thus have an impact on the quality of graduates' competencies. One policy of the Directorate of Vocational School is that students are required to take part in the program in the workplace/industry in a certain period of time. This study aims to examine the work readiness of graduates of SMK Negeri 5 Surabaya on the competency of Building Drawing Engineering based on perceptions of the workplace, principals, and productive teachers. Data collection method is conducted through focus group discussion. The results of the study show that graduates of Building Drawing Engineering of that school are ready to work according to their competencies. This study concluded that graduates of Building Drawing Engineering in SMK Negeri 5 Surabaya are ready to work because they are supported by 6 to 9 months internship. Therefore, they have 1) sufficient industrial practice experiences; (2) adequate level of basic competency mastery; and 3) highly potential work adaptation.